PENGARUH JENIS INSEKTISIDA TERHADAP LALAT BIBIT (Ophiomyia phaseoli Try.) PADA TANAMAN KEDELAI (Glycine max L.) - Yuan Cynthia Br. Simanjuntak; Yuswani Pangestiningsih; Lisnawita Lisnawita (Universitas Sumatera Utara, 2014)
Research on title effect of insecticides to control bean fly (Ophiomyia phaseoli Try.) on soybean(Glycine max L.). Using chemical insecticide to control bean fly unwisely caused pest resistance.For that purpose in this research used biology, botany, and chemical insecticide to determine theireffectiveness. This research was conducted at Kelurahan Berngam, Kecamatan Binjai Kota,Kotamadya Binjai from June to July 2013 using factorial randomized block design. The resultshowed used soursop leaf 200 gr/l of water (P1) and Bacillus thuringiensis 1 ml/l of water (P5) wereeffective to control population of bean fly with percentage of attack (0.00%) and number of larvae(0.00 larvae). Using soursop leaf 200 gr/l of water (P1) also effective to control number of bean flywas (0.00 bean fly). Time symtomp in P1 (soursop leaf 200 gram/l of water) also lower than theother treatments was six days after planted.Keywords: insecticide, Glycine max, Ophiomyia phaseoli